An Era of Change-Tolerant Systems. - Bohner, Shawn (Computer (00189162), 2007)
The article presents information on development of software systems that can adapt to changing demands. The author compares traditional software development, as of 2007, to the building of ancient Roman cities, noting that the careful planning and building makes it successful, but the success can encourage unplanned changes that weakens it. The author lists Web services, agent-based systems, and reconfigurable computing among changes effecting software's complexity. He explains the need to understand the number and intricacies of a system's interactions in order to plan for change-tolerant software, and he discusses software-change impact analysis (SCIA).